Pengaruh Pemberian Air Kelapa Muda (Cocos Nucifera L.) Terhadap Kadar Glukosa Darah Penderita Diabetes Melitus Tipe 2 pada Masyarakat Pesisir - Narmawan, Narmawan; Ananda, Siti Hadrayanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
To date the prevalence of diabetes sufferers is increasing both globally and nationally. Providing Tender Coconut Water (TCW) to reduce blood glucose levels in diabetes sufferers is a form of therapy that is practical, economical, easy to reach and easy to obtain. Moreover, coconut trees are widely spread, especially in coastal areas, so they are always available whenever you want them. Several animal studies have shown that young coconut water can be beneficial for diabetes sufferers, including its complications. However, studies in humans are currently still lacking. Therefore, this study aims to see the effect of giving young coconut water on reducing blood glucose levels in people with type 2 diabetes mellitus, especially in coastal communities. This research is a quantitative research with Quasi Experimental design with pre-test post-test with control group design. The research was conducted in the coastal area of the Nambo Community Health Center with a sample of 20 people consisting of 2 groups (10 people in the intervention group and 10 people in the control group). Statistical analysis uses independent t-test. The mean pre-test blood glucose level in the intervention group was 281.3 mg/dL while the post-test was 172.8 mg/dL. Whereas, in the control group, between pre and post, there was an increase in the average blood glucose level from 299.9 mg/dL to 326.6 mg/dL. Statistical analysis showed the p value <0.001 (p<0.05), meaning that there was a difference in average blood glucose levels between the intervention group and the control group. There is an effect of giving young coconut water or Tender Coconut Water (TCW) on blood glucose levels in people with type 2 diabetes mellitus.